1996
DOI: 10.1006/cbir.1996.0050
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Estrogen Receptor and Estrogen Effect in Mba‐15 Marrow Stromal Osteoblasts

Abstract: MBA-15, a marrow stromal-derived cell line, was shown to express an estrogen receptor. This finding was confirmed by in situ hybridization and receptor binding assay. An exposure to estrogen (10(-12)-10(-6) M) in a dose response manner resulted in a decrease of cell proliferation as measured by MTT assay. Cell function was measured by enzymatic activities of two osteoblastic markers, CD10/NEP and alkaline phosphatase. These enzymatic activities were elevated following the estrogen treatment. This model enabled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The demonstration of E 2 binding and E 2 receptor mRNA in teleost calcified tissues is consistent with the existence of E 2 receptors in mammalian and avian osteoclasts, osteoblasts, and osteoclast-and osteoblastlike cells (Eriksen et al, 1988;Komm et al, 1988;Pensler et al, 1990;Oursler et al, 1991Oursler et al, , 1994Brubaker and Gay, 1994;Fiorelli et al, 1996;Shamay et al, 1996;Hoyland et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…The demonstration of E 2 binding and E 2 receptor mRNA in teleost calcified tissues is consistent with the existence of E 2 receptors in mammalian and avian osteoclasts, osteoblasts, and osteoclast-and osteoblastlike cells (Eriksen et al, 1988;Komm et al, 1988;Pensler et al, 1990;Oursler et al, 1991Oursler et al, , 1994Brubaker and Gay, 1994;Fiorelli et al, 1996;Shamay et al, 1996;Hoyland et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…Enhanced proliferation in response to E2 by osteoblasts or marrow stromal cells was demonstrated in mouse [19,26], rat [8,9,12,13] and human cell systems [S9]. Growth inhibition was reported by Shamay et al [30], who found that reduced cell growth was also associated with increased ALP expression in a niurine stromal cell line. Inhibition of marrow stromal cell growth by E2 also appears to be consistent with ex vivo experiments indicating that the presence of estrogen in vivo reduced the proliferation of both osteoblastic and nonosteoblastic stromal cells [ 14,411. Finally, several laboratories have failed to demonstrate E2 responsiveness of osteoblastic cells or marrow stromal cells in culture [I 7,18,27].…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to the ex vivo studies demonstrating that estrogen withdrawal increased osteoblastogenesis [14,41], Qu et al [26] showed that direct E3 treatment of mouse bone marrow stromal cells in culture promoted cell proliferation as well as mineralized nodule formation. Estrogen also stimulated expression of ALP in a mouse marrow stromal cell line MBA-IS, although in this system proliferation was decreased [30]. Using human marrow stromal cell cultures, Kim and Cheng [18] found that E3 had no stimulatory effects on either proliferation or ALP expression.…”
Section: Introductionmentioning
confidence: 92%
“…Pre-osteoblastic MBA-15 cells are estrogen-receptor (ER) positive cells (Shamay et al, 1996;Benayahu, 1997) that express the SVEP1 gene which is up-regulated following modulation with 17βE 2 (Shur et al, 2006(Shur et al, , 2007. SVEP1 protein expression was also detected in human breast cancer cell lines (Shur et al, 2007).…”
Section: Introductionmentioning
confidence: 99%